Pentecostalism in Africa : presence and impact of pneumatic Christianity in postcolonial societies - Lindhardt, Martin (Global Pentecostal and Charismatic studies, 2014)
Bringing together prominent Africanist scholars from a variety of disciplines, this book offers a comprehensive treatment of the social, cultural and political impact of Pentecostal-Charismatic Christianity in postcolonial sub Saharan Africa.